Another Look at Qoheleth 7,23-29 - Clifford, Richard J. (Biblica, 2019)
Qoh 7,23-29 seems to be the conclusion of a search for wisdom that began in 7,1 in which proverbs-derived wisdom did not satisfy the sage. In his similar search in 1,12-2,26, Qoheleth adopted the persona of a king (Solomon) seeking wisdom, but instead found a wisdom that differed from the conventional version. In his search in chapter 7 (especially in v. 28), he adopted the persona of a typical suitor of Woman Wisdom, but found she did not offer him the wisdom he sought. Characteristically, Qoheleth insists on discovering truth through personal observation and so rejects revelation by Woman Wisdom. In v. 29, he rejects her assumption that her hearers are somehow deficient - scoffers, naïve, and hating knowledge. There is nothing wrong with human beings. Their searches, however, are faulty, because they place too much confidence in their own calculations.